Effect of method of preparation on hydrodesulphurization activity of Co- or Ni-promoted MoS2/SBA-15 catalysts - Garg, Shelu; Soni, Kapil; Prasad, V. V. D. N.; Kumar, Manoj; Bhaskar, Thallada; Gupta, J. K.; Dhar, G. Murali; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2014)
Ordered mesoporous material SBA-15 was synthesized and used as a support for the preparation of molybdenum sulphide catalysts through precipitation from homogeneous solution (PFHS) technique with the Mo content varying from 2-12 wt%. The prepared catalysts were evaluated for thiophene hydrodesulphurizadon catalytic activities at 400 degrees C. Catalysts prepared through PFHS method resulted in highly dispersed MoS2 catalysts, which were inferred from powder X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), low temperature oxygen chemisorptions (LTOC) and BET surface area analysis. The relationship between XPS intensity ratio, oxygen chemisorption and catalytic activities is discussed in terms of highly dispersed nano particles of MoS2 and its consequence in accommodating more promoted atoms at the edge sites.
Keywords: HDS; MoS2; PFHS method; promotional effects; SBA-15

Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.

Phase behaviour of the ternary system: monoolein-water-branched polyethylenimine - Kumar, Manoj; Kumaraswamy, Guruswamy (Soft Matter, 2015)
Addition of a branched polymer, polyethyleneimine, significantly alters the organization of a glycerol monooleate (GMO) lipid-water system. We present detailed data over a wide range of compositions (water content from 10 to 40%, relative to GMO and PEI fractions from 0 to 4%) and temperatures (25-80 degrees C). The PEI molecular weight effects are examined using polymers over a range from 0.8 to 25 kDa. Addition of PEI induces the formation of higher curvature reverse phases. In particular, PEI induces the formation of the Fd3m phase: a discontinuous phase comprising reverse micelles of two different sizes stacked in a cubic AB(2) crystal. The formation of the Fd3m phase at room temperature, upon addition of polar, water soluble PEI is unusual, since such phases typically are formed only upon addition of apolar oils. The largest stability window for the Fd3m phase is observed for PEI with a molecular weight = 2 kDa. We discuss how PEI influences the formation and stability of high curvature phases.

Fluorescent carbon nanodots for targeted in vitro cancer cell imaging - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Niryikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2016)
Carbon quantum dots (CQDs or C-dots, <= 10nm in size) are tiny carbon nanoparticles being envisaged in biosensing, bio-imaging and biomolecular/drug delivery. In the present investigation, green fluorescent carbon quantum/nano dots (GCQDs, similar to 3 nm in size) were synthesized through facile chemical slicing method. Further, folic acid (FA) functionalized GCQDs (GCQDs-FA) were obtained to enhance their targeting ability. FA is known to positively influence the binding potential and penetration into the cancer cells because of high abundance of folate receptors (FR) on various cancer cell membranes. We report high biocompatibility, photoluminescence stability and excellent in vitro cancer cell cytoplasm and nucleus targeting performance of GCQDs-FA on MCF-7 breast cancer cells. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cancer cell bio-imaging; Carbon quantum/nano dots; Cell cytoplasm and nucleus targeting; Green fluorescence; Photoluminescence stability; Targeting ability

Aqueous dispersions of lipid nanoparticles wet hydrophobic and superhydrophobic surfaces - Kumar, Manoj; Kulkarni, Mayuresh A.; Chembu, Narendiran G.; Banpurkar, Arun; Kumaraswamy, Guruswamy (Soft Matter, 2018)
Efficient delivery of aqueous sprays to hydrophobic surfaces is the key technological challenge in a wide variety of applications, including pesticide delivery to plants. To account for losses due to bouncing of pesticide sprays off hydrophobic leaf surfaces, a large excess of pesticide is typically employed, resulting in environmentally hazardous run-offs that contaminate soil and ground water. We demonstrate that aqueous dispersions of glycerol monooleate nanoparticles, called cubosomes, wet hydrophobic and superhydrophobic surfaces and adhere to them. Cubosomes comprise glycerol monooleate lipid molecules self-assembled into a double diamond cubic phase, that form stable aqueous dispersions that are sterically stabilized using amphiphilic block copolymers. We use high speed imaging to monitor the spreading and retraction of aqueous drops impinged on model hydrophobic substrates and on superhydrophobic lotus leaves. We show that cubosomes diffuse to hydrophobic substrates and reorganize to form a thin, approximate to 2 nm adsorbed lipid layer during the millisecond time scales that characterize drop impact. This adsorbed film drastically reduces the water contact angle, transforming the hydrophobic surface to hydrophilic, thus facilitating retention of the aqueous drop on the surface. Aqueous drops of cubosomes impinged at low velocities on inclined natural superhydrophobic lotus leaf surfaces do not roll off, unlike drops of water or surfactant solutions. When sprayed on inclined lotus leaves, corresponding to the case of high velocity drop impingement, cubosome dispersions form a continuous wetting film. Our results have important implications for efficient, environment-friendly delivery of pesticide sprays.

Large PAMAM dendron induces formation of unusual P4332 mesophase in monoolein/water system - Kumar, Manoj; Patil, Naganath Ganapatarao; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Langmuir, 2018)
Compact macromolecular dendrons have been shown to induce the formation of discontinuous inverse micellar assemblies with Fd3m symmetry in monoolein/water systems. Here, we demonstrate that a large PAMAM dendron (G5: fifth generation) induces the formation a very unusual mesophase with P4332 symmetry. This mesophase had previously been observed in monoolein/water systems only on addition of cytochrome C. The P4332 mesophase can be considered an intermediate phase between the bicontinuous Ia3d and discontinuous micellar mesophases. In this unusual phase, every third rod junction of the Ia3d mesophase is replaced with a spherical micelle. We present a detailed investigation of the phase behaviour of monoolein/water as a function of G5 concentration and temperature. Addition of 1% G5 in 85/15 monoolein/water system induces a transition from the L to Ia3d phase. Further increase in G5 concentration to above 2% induces the formation of the P4332 phase. Thus, incorporation of G5 yields a qualitatively different phase diagram when compared with incorporation of lower generation PAMAM dendrons (G2 – G4) in monoolein/water, where the reverse micellar Fd3m phase forms. PAMAM dendrons of all generations, G2 – G5, bear terminal amine groups that interact with the monoolein head group. The compact molecular architecture of the dendrons and these attractive interactions induce bending of the monoolein bilayer structure. For smaller dendrons, G2 – G4, this results in the formation of the Fd3m phase. However, the large size of the G5 dendron precludes this and a rare intermediate phase between the Ia3d and discontinuous micellar phase, the P4332 mesophase forms instead.

Fluorescent carbon nanodots for targeted in vitro cancer cell imaging (vol 4, pg 71, 2016) - Aiyer, Sandhya; Prasad, Rajendra; Kumar, Manoj; Nirvikar, K.; Jain, Bhanprakash; Kushwaha, Omkar S. (Applied Materials Today, 2019)

Francisella novicida Cas9 interrogates genomic DNA with very high specificity and can be used for mammalian genome editing - Acharya, Sundaram; Mishra, Arpit; Paul, Deepanjan; Ansari, Asgar Hussain; Azhar, Mohd; Kumar, Manoj; Rauthan, Riya; Sharma, Namrata; Aich, Meghali; Sinha, Dipanjali; Sharma, Saumya; Jain, Shivani; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Genome editing using the CRISPR/Cas9 system has been used to make precise heritable changes in the DNA of organisms. Although the widely used Streptococcus pyogenes Cas9 (SpCas9) and its engineered variants have been efficiently harnessed for numerous gene-editing applications across different platforms, concerns remain regarding their putative off-targeting at multiple loci across the genome. Here we report that Francisella novicida Cas9 (FnCas9) shows a very high specificity of binding to its intended targets and negligible binding to off-target loci. The specificity is determined by its minimal binding affinity with DNA when mismatches to the target single-guide RNA (sgRNA) are present in the sgRNA:DNA heteroduplex. FnCas9 produces staggered cleavage, higher homology-directed repair rates, and very low nonspecific genome editing compared to SpCas9. We demonstrate FnCas9-mediated correction of the sickle cell mutation in patient-derived induced pluripotent stem cells and propose that it can be used for precise therapeutic genome editing for a wide variety of genetic disorders.
Keywords: CRISPR Cas9; gene therapy; Genome editing; iPSCs; sickle cell anemia

FnCas9-based CRISPR diagnostic for rapid and accurate detection of major SARS-CoV-2 variants on a paper strip - Kumar, Manoj; Gulati, Sneha; Ansari, Asgar H.; Phutela, Rhythm; Acharya, Sundaram; Azhar, Mohd; Murthy, Jayaram; Kathpalia, Poorti; Kanakan, Akshay; Maurya, Ranjeet; Vasudevan, Janani Srinivasa; Aparna, S.; et al. (eLife, 2021)
The COVID-19 pandemic originating in the Wuhan province of China in late 2019 has impacted global health, causing increased mortality among elderly patients and individuals with comorbid conditions. During the passage of the virus through affected populations, it has undergone mutations, some of which have recently been linked with increased viral load and prognostic complexities. Several of these variants are point mutations that are difficult to diagnose using the gold standard quantitative real-time PCR (qRT-PCR) method and necessitates widespread sequencing which is expensive, has long turn-around times, and requires high viral load for calling mutations accurately. Here, we repurpose the high specificity of Francisella novicida Cas9 (FnCas9) to identify mismatches in the target for developing a lateral flow assay that can be successfully adapted for the simultaneous detection of SARS-CoV-2 infection as well as for detecting point mutations in the sequence of the virus obtained from patient samples. We report the detection of the S gene mutation N501Y (present across multiple variant lineages of SARS-CoV-2) within an hour using lateral flow paper strip chemistry. The results were corroborated using deep sequencing on multiple wild-type (n = 37) and mutant (n = 22) virus infected patient samples with a sensitivity of 87% and specificity of 97%. The design principle can be rapidly adapted for other mutations (as shown also for E484K and T716I) highlighting the advantages of quick optimization and roll-out of CRISPR diagnostics (CRISPRDx) for disease surveillance even beyond COVID-19. This study was funded by Council for Scientific and Industrial Research, India.

Rapid and accurate nucleobase detection using FnCas9 and its application in COVID-19 diagnosis - Azhar, Mohd; Phutela, Rhythm; Kumar, Manoj; Ansari, Asgar Hussain; Rauthan, Riya; Gulati, Sneha; Sharma, Namrata; Sinha, Dipanjali; Sharma, Saumya; Singh, Sunaina; Acharya, Sundaram; Sarkar, Sajal; et al. (Biosensors & Bioelectronics, 2021)
Rapid detection of DNA/RNA pathogenic sequences or variants through point-of-care diagnostics is valuable for accelerated clinical prognosis, as witnessed during the recent COVID-19 outbreak. Traditional methods relying on qPCR or sequencing are tough to implement with limited resources, necessitating the development of accurate and robust alternative strategies. Here, we report FnCas9 Editor Linked Uniform Detection Assay (FELUDA) that utilizes a direct Cas9 based enzymatic readout for detecting nucleobase and nucleotide sequences without transcleavage of reporter molecules. We also demonstrate that FELUDA is 100% accurate in detecting single nucleotide variants (SNVs), including heterozygous carriers, and present a simple web-tool JATAYU to aid end-users. FELUDA is semi-quantitative, can adapt to multiple signal detection platforms, and deploy for versatile applications such as molecular diagnosis during infectious disease outbreaks like COVID-19. Employing a lateral flow readout, FELUDA shows 100% sensitivity and 97% specificity across all ranges of viral loads in clinical samples within 1hr. In combination with RT-RPA and a smartphone application True Outcome Predicted via Strip Evaluation (TOPSE), we present a prototype for FELUDA for CoV-2 detection closer to home.
Keywords: CRISPRDx; FELUDA; FnCas9; LFA; SARS-CoV2; SNV detection